The World My Wilderness and the Possibility of Forgiveness: War, Guilt, Atonement. Issue 2 (17th February 2022) - Hepburn, Allan
ABSTRACT: In Rose Macaulay's The World My Wilderness (1950), forgiveness affords possibilities to redeem personal and national guilt. Can humankind be forgiven for atrocities perpetrated during the Second Word War, and if so, by whom? Whereas forgiveness can undo the predicament of irreversibility by bringing about reconciliation and an improved future for individuals and communities, those outcomes never come to pass in this novel. Refusal to acknowledge guilt thwarts the likelihood that the future of Europe will differ from the past. Critics usually dismiss Macaulay's religious thinking as irrelevant, but she freely adapts Christian ideas about atonement and forgiveness to this narrative about guilt. This essay draws upon a wide range of Macaulay's fictional and critical works, such as Some Religious Elements in English Literature, The Towers of Trebizond, essays about Jonathan Swift and "Religious Writing, " and her biography of John Milton, to argue that wartime guilt and forgiveness regulate midcentury novelistic representation.